(3w-5)(2w)(w+7)=0

Simple and best practice solution for (3w-5)(2w)(w+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3w-5)(2w)(w+7)=0 equation:


Simplifying
(3w + -5)(2w)(w + 7) = 0

Reorder the terms:
(-5 + 3w)(2w)(w + 7) = 0

Remove parenthesis around (2w)
(-5 + 3w) * 2w(w + 7) = 0

Reorder the terms:
(-5 + 3w) * 2w(7 + w) = 0

Reorder the terms for easier multiplication:
2w(-5 + 3w)(7 + w) = 0

Multiply (-5 + 3w) * (7 + w)
2w(-5(7 + w) + 3w * (7 + w)) = 0
2w((7 * -5 + w * -5) + 3w * (7 + w)) = 0
2w((-35 + -5w) + 3w * (7 + w)) = 0
2w(-35 + -5w + (7 * 3w + w * 3w)) = 0
2w(-35 + -5w + (21w + 3w2)) = 0

Combine like terms: -5w + 21w = 16w
2w(-35 + 16w + 3w2) = 0
(-35 * 2w + 16w * 2w + 3w2 * 2w) = 0
(-70w + 32w2 + 6w3) = 0

Solving
-70w + 32w2 + 6w3 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), '2w'.
2w(-35 + 16w + 3w2) = 0

Factor a trinomial.
2w((-7 + -1w)(5 + -3w)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0

Subproblem 2

Set the factor '(-7 + -1w)' equal to zero and attempt to solve: Simplifying -7 + -1w = 0 Solving -7 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1w = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1w = 0 + 7 -1w = 0 + 7 Combine like terms: 0 + 7 = 7 -1w = 7 Divide each side by '-1'. w = -7 Simplifying w = -7

Subproblem 3

Set the factor '(5 + -3w)' equal to zero and attempt to solve: Simplifying 5 + -3w = 0 Solving 5 + -3w = 0 Move all terms containing w to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3w = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3w = 0 + -5 -3w = 0 + -5 Combine like terms: 0 + -5 = -5 -3w = -5 Divide each side by '-3'. w = 1.666666667 Simplifying w = 1.666666667

Solution

w = {0, -7, 1.666666667}

See similar equations:

| 2/3*x=18 | | x(4x)=5 | | 2+4s=10 | | 15.51-9.40=x | | 3x+4-6y+x+3y= | | 1-3x=3x+2 | | -34+u=-50 | | 7=t-79/2 | | 15(12+8a)= | | 6(b+3)=78 | | x+(-32)=-48 | | 7*x-4=31 | | 2+3.8=x+4.7 | | .5(x-6)=(1/4)x-(2/5) | | 12=p/3+11 | | -28+y=-12 | | c/3-2=2 | | 7=(x)(135) | | 7/3*y=14/3 | | 3x3/5=? | | 13+y=12 | | 5x-135=90 | | (50-χ)/0,4 | | -5x-1/3=29/3 | | 30+4x=150 | | 32=-12x-x^2 | | (2011334-x)/0,04= | | 32=-12x-x^3 | | (2011334-χ)/0,04 | | 10c+3c(c-7)=18 | | 8+216= | | 25+4.5*75=40+25*75 |

Equations solver categories